2021
DOI: 10.1117/1.jmi.8.1.010901
|View full text |Cite
|
Sign up to set email alerts
|

Quick guide on radiology image pre-processing for deep learning applications in prostate cancer research

Abstract: . Purpose : Deep learning has achieved major breakthroughs during the past decade in almost every field. There are plenty of publicly available algorithms, each designed to address a different task of computer vision in general. However, most of these algorithms cannot be directly applied to images in the medical domain. Herein, we are focused on the required preprocessing steps that should be applied to medical images prior to deep neural networks. Approach: To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…The three-dimensional equivalent of a pixel is a voxel. 25 Radiodensity in CT Scans is quantified by means of the Hounsfield Unit (HU), which depends on the absorption/attenuation coefficient of the tissue under consideration. Distilled water (at a standardized temperature and pressure) is arbitrarily assigned a HU value of 0, whereas air is designated as À1000.…”
Section: A Windowingmentioning
confidence: 99%
“…The three-dimensional equivalent of a pixel is a voxel. 25 Radiodensity in CT Scans is quantified by means of the Hounsfield Unit (HU), which depends on the absorption/attenuation coefficient of the tissue under consideration. Distilled water (at a standardized temperature and pressure) is arbitrarily assigned a HU value of 0, whereas air is designated as À1000.…”
Section: A Windowingmentioning
confidence: 99%
“…Now, we discuss the network in detail: Feature Generation: During manual analysis, a radiologist uses HU windowing to adjust CT intensity values to focus on organs/tissues of interest. Inspired by Masoudi et al [15], we mimic the radiologist's behaviour in our ULD and highlight multiple organs of interest with heuristically determined 5 HU windows [16]:…”
Section: Methodsmentioning
confidence: 99%
“…Now, we discuss the network in detail: Feature Generation: During manual analysis, a radiologist uses HU windowing to adjust CT intensity values to focus on organs/tissues of interest. Inspired by Masoudi et al[15], we mimic the radiologist's behaviour in our ULD and highlight multiple organs of interest with heuristically determined 5 HU windows[16]:U 1 = [400, 2000], U 2,3 = [−600, 1500], [50, 350], U 4 = [30, 150], U 5 = [50, 400] for bones, chest region including lungs & mediastinum, abdomen including liver & kidney, and soft-tissues, respectively. After windowing, 3-channel multi-intensity image (I Ui ) is passed as input to the ResNeXt-101 shared backbone with feature…”
mentioning
confidence: 99%
“…The different Python packages used during this study can be found in Supplementary Table S1. Pre-processing of MRI is essential for ML purposes, for reducing scanner dependence, and for ensuring reproducibility (39)(40)(41). As there is, to date, no consensus regarding the best way to pre-process MRI for our purposes, three different pre-processing workflows were applied and compared: " minimalist" , standardization, and "harmonization".…”
Section: Pre-processing Of Brain Mri Datamentioning
confidence: 99%